Optimization of Solid State Fermentation Condition to Increase Total Phenolic Content and Antioxidant Activity in Seaweed (Kappaphycus Alvarezii) Extract - M.N, Norakma; A.H, Zaibunnisa; L.W, Lai; R, Givitha; Razarinah W. A. R, Wan (International Journal of Engineering and Technology, 2019)
Conventional techniques such as solvent extraction can be effectively used to extract free phenolic compounds in plants. However, this method is inefficient to extract bound phenolics. Solid state fermentation (SSF) approach with Aspergillus oryzae was used to enhance bioavailability of polyphenols in Kappaphycus alvarezii. A set of experiment was computed by face centered central composite design (FCCCD) to optimize the fermentation parameters based on maximum phenolic content and antioxidant activity. Four independent variables namely: time (0, 4 and 8 days), temperature (28, 30 and 32 Â°C), initial moisture content (60, 70 and 80 %) and inoculum level (10, 20 and 30 % (v/v)) were investigated. The experimental results for both TPC and DPPH were 9.449 Â± 0.198 mg GAE/g and 87.135 Â± 0.857 % of scavenging activity, respectively; where both responses were in good agreement with RSM model prediction. The RSM design used has been proven to successfully predict the total phenolic content and antioxidant activity. Fermentation condition with 70% initial moisture content, 10% (v/v) inoculum level, performed at 30oC for 4 days was found to produce maximum TPC and DPPH radical scavenging activity of Kappaphycus alvarezii.Â Â